The Flat Dilatometer Test in an Unsaturated Tropical Soil Site - Rocha, Breno Padovezi (2021)
The site characterization of unsaturated soils is well stablished based on laboratory tests, which are expensive and time-consuming. In-situ testing methods, such as the flat dilatometer test (DMT), are an alternative to the traditional approach of drilling, sampling, and laboratory testing. The literature on DMT interpretation is well established on saturated and well-behaved soils. Only few studies deal with DMT interpretation in unusual soils, and little is known about the influence of soil suction on this test. This paper presents and discusses the influence of soil suction on four DMT campaigns carried out in an unsaturated tropical soil site, also incorporating the soil suction influence on the DMT interpretation. Soil suction was estimated by the soil–water characteristic curve (SWCC) and water content profiles. The water content profiles range from 11.3 to 19.7% which corresponds to a suction range estimated by SWCCs mostly between 6 and 200 kPa. Soil suction significantly influenced DMT data up to 5 m depth at the studied site (the unsaturated active zone) increasing the intermediate DMT parameters. The average horizontal stress index (KD) was equal to about 1.7 and the average dilatometer modulus (ED) was about 4.7 MPa in the active zone and practically doubled their values due to in situ soil suction. The estimated peak friction angle (ϕ) was 20–30% higher due to soil suction influence on DMT assuming the soil behaves as a sand like material. Soil suction must be considered to assess the behavior of the investigated soil by the DMT. The suction influence should be incorporated in the effective stress and this approach considerably improved the site characterization of the studied site.